Guidelines for the stabilization of a polar rhombohedral phase in epitaxial Hf0.5Zr0.5O2 thin films. Issue 1 (9th December 2020) - Nukala, Pavan; Wei, Yingfen; de Haas, Vincent; Guo, Qikai; Antoja-Lleonart, Jordi; Noheda, Beatriz
Abstract: The unconventional Si-compatible ferroelectricity in hafnia-based systems, which becomes robust only at nanoscopic sizes, has attracted a lot of interest. While a metastable polar orthorhombic (o-) phase ( Pca21 ) is widely regarded as the responsible phase for ferroelectricity, a higher energy polar rhombohedral (r-) phase is recently reported on epitaxial HfZrO4 (HZO) films grown on (001) SrTiO3 ( R3m or R3 ), (0001) GaN ( R3 ), and Si (111). Armed with results on these systems, here we report a systematic study leading toward identifying comprehensive global trends for stabilizing r-phase polymorphs in epitaxially grown HZO thin films (6 nm) on various substrates (perovskites, hexagonal and Si).